THE INFLUENCE OF SERVICE QUALITY AND CONSUMER BEHAVIOR ON YAMAHA MOTORCYCLE PURCHASE DECISIONS (Case Study On CV. Sekawan Motor In The City Of Kefamenanu) - Bernadus Ghawa Rado; Emilia Khristina Kiha; Alwin A. Kadir (Jurnal Ekonomi, 2022)
Motorcycle manufacturers sell their products in various ways so that their products can be sold and can reach the specified target. It's the same with sales of Yamaha motorcycles that occurred in CV. Sekawan Motor in the city of Kefamenanu which sells its products has not met the specified target. This is due to the trust of the people of the city of Kefamenanu in choosing motorbikes, prioritizing motorbikes from competing Yamaha brands such as Honda and Suzuki. Consideration before buying is a factor in purchasing decisions for Yamaha, but the decision-making system for buying Yamaha takes a long time because of the negative side of the Yamaha brand. This is what prompted researchers to conduct research on CV. Sekawan Motor in the city of Kefamenanu. The purpose of this study is to determine the effect of service quality and consumer behavior on purchasing decisions for Yamaha motorbikes (Case Study on CV. Sekawan Motor in Kefamenanu City). The research method used secondary data with a total sample of 69 people and the data analysis technique used multiple linear regression which was processed using the SPSS program. From the results of SPSS processing, it was obtained that partially and simultaneously there was a positive and significant influence between service quality and consumer behavior on purchasing decisions for Yamaha motorbikes at CV. Sekawan Motor in the city of Kefamenanu.